Ninth Five Year Plan 1997 and Annual Plan 1997-1998 (Scheme-Wise Details) Government of Pondicherry Planning and Research Department - Planning Commission (Planning Commission, 1997)
The Territory constitutes a single district consisting of 264 census villages, 129 revenue villages, 4 subtaluks and 2 taluks. For the purpose of development administration the Territory is divided into 6 blocks consisting of 47 circles of village level workers. Pondicherry Panchayats Act of 1973 and Municipalities Act of 1973 came into force in 1974. There are 5 Municipalities, namely, Pondicherry, Ozhukarai, Karaikal, Mahe and Yanam. There are 10 commune Panchayats - 5 in Pondicherry region, namely, Villianur, Mannadipet, Ariankuppam, Bahour, Nettapakkam and 5 in Karaikal region, namely, Thirunallar, Neravy, Nedungadu, Kottucherry and T.R.Pattinam.
Scheme-Wise Details
Government of Pondicherry